Interreligious Dialogue in the Thought of Benedict XVI: Ecclesiological Foundations and Distinctive Characteristics - Viviano, Rocco (Annales Missiologici Posnanienses, 2015)
Since the Second Vatican Council, Catholic teaching has placed great emphasis on in interreligious dialogue as an integral aspect of the Church’s mission. However there remains a tension between interreligious dialogue and the church’s duty of proclaiming the gospel that constantly calls for clarification. By articulating the ecclesiological foundations of interreligious dialogue, Benedict XVI has significantly contributed to clarify the Catholic understanding of its nature and characteristics, and also suggested concrete ways in which Christians and the followers of other religions are called to engage in constructive dialogue for the good of the whole of humanity.